Управління капітaлом підприємства як фактoр йoгo стaлoго рoзвитку - Доренський, Євген В'ячеславович (НТУ "ХПІ", 2017)
У статті розглядаються особливості формування структури капіталу підприємства, обґрунтовується необхідність управління нею, запропонована модель управління капіталом підприємства в ринкових умовах, проведені дослідження сучасних тенденцій формування капіталу в Україні.

In the article features of formation of the capital structure of the enterprise are considered, the necessity of its management is proved, the model of enterprise capital management in market conditions is offered, the modern tendencies of capital formation in Ukraine are investigated.
Managing the company's capital as a factor of its sustainable development
Keywords: власний капітал; позиковий капітал; оптимізація; фінансовий менеджмент; enterprise capital; equity capital; borrowed capital; capital management; capital optimization